Travelling wave solutions of generalized Klein-Gordon equations using Jacobi elliptic functions - Ates, Esma; İnç, Mustafa (Springer, 2017)
This paper obtains exact travelling wave solutions of five various forms of the generalized nonlinear Klein-Gordon equations using Jacobi elliptic functions. Topological and non-topological soliton solutions are obtained as well as Jacobi elliptic function solutions. It is acquired constraint conditions for the existence of solitons.
Keywords: Klein-Gordon equation; Jacobi elliptic functions; Solitons; Travelling wave solutions